Chest Radiology: A Resident's Manual - Kirchner, J. Johannes (Thieme, 2011)
Chest Radiology: A Resident's Manual is a comprehensive introduction to reading and analyzing radiologic cardiopulmonary images. Readers are guided through systemic image analysis and can further enhance their learning experience with training cases found at the end of each chapter. Cases describe and discuss frequently asked questions regarding heart failure, bronchitis, pneumonia, bronchial carcinoma, fibrosis, pleural disorders, and more. This user-friendly manual will allow the reader to confidently answer the most important and commonly encountered questions related to plain chest radiographs in daily clinical practice. The easy-to-read layout pairs explanatory text on the left page with related drawings and images on the right, allowing readers to navigate their way through each section with ease.